Sympathetic Orientalism and the Mediation of Islamic Theology in the Film Kingdom of Heaven - Muzaki Muzaki; Muhamad Hilmi Pauzian; Asniah Asniah (Khazanah Theologia, 2025)
In the context of post-9/11 Islamophobia and rising global religious nationalism, Hollywood cinema has evolved from explicit orientalism toward subtle representational strategies that appear progressive while maintaining Western epistemological hegemony. Despite ostensibly positive portrayals, contemporary films may perpetuate cultural hierarchies through sophisticated soft power mechanisms. This study examines how Ridley Scott's Kingdom of Heaven (2005) employs sympathetic orientalism positive portrayals of Islam conditional upon conformity with Western secular values and analyzes implications for indigenous pluralism discourse in Indonesia as a Muslim-majority society. Using Postcolonial Critical Discourse Analysis (PCDA), we systematically analyzed 12 key Muslim-Christian interaction scenes (47 minutes total) and 87 visual sequences from the Director's Cut (194 minutes), examining dialogue patterns, character construction, cinematography, and mise-en-scène. Analysis integrated five Indonesian pluralism policy documents to explore intersections between global media narratives and local tolerance frameworks. The film constructs "acceptable Muslims" through three mechanisms: hierarchical character construction privileging secular rationality (83% of positive Muslim representations require Western values with zero Islamic theological references), visual semiotics that aestheticize yet distance Islamic civilization (Christian sites receive 57% more screen time with eye-level humanizing shots versus high-angle exotic framing for Islamic spaces), and conditional inclusion through mimicry requiring Muslims to adopt Western epistemological standards. Statistical analysis reveals rational characters receive significantly more stable cinematography than religious characters (χ² = 12.4, p < 0.01). Sympathetic orientalism operates as evolved hegemonic strategy more ideologically powerful than explicit stereotypes by concealing epistemological hierarchies behind progressive rhetoric. This potentially marginalizes Indonesia's indigenous pluralism models based on Bhinneka Tunggal Ika and Islamic principles, replacing them with Western liberal-secular frameworks. Contribution: This study advances sympathetic orientalism as a novel analytical framework for understanding contemporary soft power in global media, revealing how ostensibly progressive representations undermine authentic indigenous approaches to religious diversity management in Muslim-majority societies